2018
DOI: 10.1016/j.agwat.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of plastic film mulching on crop yields, soil water, nitrate, and organic carbon in Northwestern China: A meta-analysis

Abstract: HighlightsOur study can provide a comprehensive assessment on the impacts of the plastic film mulching.We assessed the effects of plastic film mulching on soil physical and biochemical properties.The spring maize yield was significantly increased with plastic film mulching in Northwest China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(81 citation statements)
references
References 36 publications
9
70
2
Order By: Relevance
“…Meanwhile black plastic-film mulch created suitable thermal conditions and a relatively good aeration environment for potato growth in this study. Black plastic-film mulch also increased soil mineral N concentration, reduced evaporation from the soil surface in addition to modifying soil temperature, reduced irrigation water input, and improved water use efficiency as reported by Ma et al [33].…”
Section: Discussionsupporting
confidence: 63%
“…Meanwhile black plastic-film mulch created suitable thermal conditions and a relatively good aeration environment for potato growth in this study. Black plastic-film mulch also increased soil mineral N concentration, reduced evaporation from the soil surface in addition to modifying soil temperature, reduced irrigation water input, and improved water use efficiency as reported by Ma et al [33].…”
Section: Discussionsupporting
confidence: 63%
“…Zhang et al studied the effect of mulching film on the productivity of maize and reported an average increase of 58% in the production. Similar studies were carried out by Li et aland Ma et al wherein it was concluded that using black‐colored mulching film served much better as compared with gravel‐sand or straws. It was also reported that by using mulching film, the transport of N 2 O from soil to the atmosphere was reduced, which further enhanced the N 2 O consumption by plants by diffusion process .…”
Section: Introductionsupporting
confidence: 77%
“…Our dataset showed that yields under CRR peaked at 200 to 300 kg ha −1 of N, whereas 100 to 200 or >300 kg N ha −1 showed no significant results. A recent meta-analysis by Ma et al (2018) also found that both wheat and maize benefitted the most from mulching when N was applied at 200 to 300 kg ha −1 . Particularly noteworthy are the reports by Li et al (2015) and Sui et al (2016), which found that the optimal N dose for wheat was 75 to 180 kg ha −1 for the Guanzhong Plain in China's Shaaxi Province and 140 to 190 kg ha −1 for North China, respectively.…”
Section: Wheat Yield Under Different Doses Of Nitrogenmentioning
confidence: 95%